Las tic y su influencia en el proceso de enseñanza aprendizaje en los estudiantes del 4to año EGB en la UE Alfredo Noboa Montenegro, Caluma. 2022 - Villegas Peñafiel, Mario Alejandro (2022)
In recent years, technological advances have played a very important and transcendental role in our society, as well as in different educational contexts. The purpose of this case study is to determine the impact of ICT to favor the teaching-learning process of students who are in the 4th year of basic general education (EGB); The research was carried out under the qualitative research approach, where instruments such as the survey, observation and interview with teachers were used in order to determine how it can benefit, adapt, facilitate and optimize the use of ICTs in education, which allowed obtaining relevant, adequate and suitable information on the problem raised. The results of this research showed that, in educational settings, the adoption of ICT is often considered a very demanding challenge that generally meets with resistance to its use or implementation. Although it is widely believed that decades of large investments in ICT and the growing digitalization of teaching and learning processes can benefit and favor the educational system at different academic levels and improve the quality and warmth of study in students.